ONLINE AND BLENDED LEARNING: EFFECTIVE METHODS FOR LANGUAGE TEACHING (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The importance of blended learning in teaching foreign languages is addressed and provides viewpoints on the importance of blended learning in enhancing students` knowledge, skills and competencies in language learning in the modern learning process.  Today, much attention is paid to a radical change in the way English is taught. Students are becoming more involved in learning foreign languages through online learning with a teacher in collaboration and developing language skills.